2021
DOI: 10.1111/bjd.20873
|View full text |Cite
|
Sign up to set email alerts
|

Nemolizumab plus topical agents in patients with atopic dermatitis (AD) and moderate‐to‐severe pruritus provide improvement in pruritus and signs of AD for up to 68 weeks: results from two phase III, long‐term studies*

Abstract: The trial sponsor was involved in the study design, the collection, analysis, interpretation of data, and the decision to submit the article for publication. Maruho also paid for professional writing assistance. Nemolizumab and placebo were provided by the product manufacturer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 43 publications
0
42
0
1
Order By: Relevance
“…Nemolizumab significantly reduces the itch, as well as AD severity compared to placebo [ 55 ]. Moreover, the results from two phase III long-term studies in patients with atopic dermatitis have confirmed that the use of nemolizumab with topical treatments produces even greater, continuous improvement in pruritus, signs of the disease, and patients’ QoL [ 56 ]. Similar findings were observed in the treatment of chronic prurigo.…”
Section: Discussionmentioning
confidence: 99%
“…Nemolizumab significantly reduces the itch, as well as AD severity compared to placebo [ 55 ]. Moreover, the results from two phase III long-term studies in patients with atopic dermatitis have confirmed that the use of nemolizumab with topical treatments produces even greater, continuous improvement in pruritus, signs of the disease, and patients’ QoL [ 56 ]. Similar findings were observed in the treatment of chronic prurigo.…”
Section: Discussionmentioning
confidence: 99%
“…dupilumab, tralokinumab, lebrikizumab and nemolizumab). 40 47 Whether and how these cytokines affect the complex and inter-dependent epidermal structures that result in a healthy barrier is still being studied.…”
Section: Historical Perspective On Ad Skin Barrier Defectsmentioning
confidence: 99%
“…The H4R antagonist adriforant slightly improved disease severity without statistically significant effects on pruritus in a phase IIa study [ 49 ], and further programs for H4R antagonists for AD have been suspended [ 3 , 49 ]. The anti-IL-31 ab nemolizumab significantly reduced pruritus in AD and prurigo nodularis [ 50 , 51 ]. IL-31 is produced by several T2 cells such as Th2 cells, mast cells, macrophages, and dendritic cells, activates neurons via IL-31Rα, TRPV1 or TRPA1, and further induces the recruitment of T cells by chemotactic cytokines along with increases of neuronal branching in the skin in a vicious cycle [ 3 , 36 , 52 ].…”
Section: Evidence That Skin Barrier Dysfunction Is a Key Precursor Of Admentioning
confidence: 99%